ACADEMIC WRITING CENTER AT THE HIGHER SCHOOL OF ECONOMICS - Evgeny V. Bakin (Высшее образование в России)
The article sheds light upon Academic Writing Center, an educational project launched at the Higher School of Economics in September 2011. The author briefly mentions the center’s objectives, explores the programs offered for potential students and unveils the questions of recruitment, timing and strategic planning. At the end some statistics is given.